Assessing the Influence of Various Work Breakdown Structures on Project Completion Time - Odedairo, Babatunde Omoniyi (Engineering, Technology & Applied Science Research, 2024)
In project management, a clear definition of the objective is required for the success of a project. Scope management is a performance indicator used to ascertain compliance with predefined project boundaries. The Work Breakdown Structure (WBS) is an essential part of the scope management process and a tool in project planning. Although there is much research on WBS, there is a lack of information regarding the relationship between the selection of WBS orientation and project completion time. In this paper, the influence of alternative WBS orientations on project completion time is assessed. The Project Life Cycle (PLC) and technology (T) WBS were applied across two projects—the construction of a Liquefied Petroleum Gas (LPG) facility and the Renovation of an Office Complex (ROC)—using a top-down decomposition methodology. The PLC-WBS and T-WBS were created utilizing Figma software. The project duration was determined using the critical path method, which was implemented in the Python programming language. Based on WBS selection, differences were discovered in the definition of the project deliverables, network construction, and aggregation of work packages. These discrepancies had an impact on the technological relationships between activities by reducing opportunities for parallel processing. The LPG project was completed in 86 days using the PLC-WBS and in 80 days using the T-WBS orientation. For ROC, the project can be accomplished within 128 and 126 days, using the PLC-WBS and T-WBS orientation, respectively. This outcome suggested that there might be an association between the WBS and the project objective. Therefore, an assessment of different WBSs in project scope management demonstrated their potential influence on decision-making in activity planning and scheduling, network construction, and project objectives.